Cesarean Scar Ectopic Pregnancy: Experience From Benghazi Medical Center, 2022 - Muna.I. Al Shawbaki; Fawzia .H. El. Harary; Aziza Elgathafi; Amina Abdulla Al Shekteria (Sirte Journal of Medical Sciences, 2023)
Background: Cesarean scar pregnancy (CSP) is a rare consequence of a previous cesarean delivery and a new type of ectopic pregnancy, but it is life-threatening if unrecognized and inadequately managed. Despite the rising incidence of CSP, there are no consensus or evidence-based guidelines for management. Aims: To review risk factors, clinical features, diagnostic methods, and management of women with CSP at Benghazi Medical Center. Materials and methods: A descriptive-case series study of CSP cases between the Ist of March 2018 and Ist of April 2022.. Data collected retrospectively. The data included demographics, presenting symptoms and signs, ultrasound findings, treatment used, and any complications. Results: The total number of ectopic pregnancies in period between 1st March 2018 and 1st April 2022 was 262, ten women (3.82%) were diagnosed as scar ectopic, The women’s ages ranged from 28 to 47 years, about 60% had three or four previous cesarean scars, abdominal pain with vaginal bleeding was in 30% of the cases, while 60% of patients were asymptomatic and all patients were stable during the diagnosis, except for one case that had signs of shock. ultrasound finding was 80% presence of gestational sac implanted low near the previous scar; initial diagnosis was delayed by 50%. The management was laparotomy and gestational sac excision in four cases that did not require further treatment, dilatation and uterine evacuation were done in two cases that required use of uterine balloon to control bleeding and further use of methotrexate In one case (10%), systemic methotrexate alone was effective. Severe bleeding was seen among 60% of women, and 20% underwent hysterectomy. The complications were significantly (P< 0.05) more common among women with high parity and also in cases where there was no intervention during the diagnosis. Conclusion: A previous uterine scar is the main risk factor for CSP; there is no specific clinical feature for CSP; ultrasound is used for the diagnosis; surgical management appears to be a better option, serious complications were seen mainly when no intervention was done during the diagnosis.